Bimetallic Pt-Ni catalysts supported on usy zeolite for n-hexane isomerization - Barsi,F. V. (2009)
Isomerization of linear alkanes has had considerable importance for the refining industry because the isomers formed in this reaction have high octane number. Most works reported in the literature studied the use of bifunctional catalysts, i.e., ones that have acid sites and metallic sites. In this study, bifunctional monometallic (Ni or Pt) and bimetallic catalysts (Pt-Ni), using HUSY zeolite as the support, were prepared in order to verify the role of the metal content and composition on the catalytic properties for n-hexane isomerization. The method used for metal dispersion in the zeolite was competitive ion exchange using ammine complexes [Ni(NH3)6]Cl2 and [Pt(NH3)4]Cl2 as precursors. Four series of catalysts with constant atomic metal content had total metal amounts between 130 and 280 µmol M/g cat. Catalysts were characterized by temperature programmed reduction (TPR) and subjected to catalytic evaluation for n-hexane isomerization at 250 ºC and 1 atm using H2/C6 = 9 molar ratio. TPR results show an easier reducibility of Ni+2 cations in the presence of Pt, which was evidenced by the displacement of the reduction peak of those cations towards lower temperatures in bimetallic catalysts. The bimetallic catalysts presented a higher activity in the isomerization of n-hexane when compared to the monometallic ones, as well better stability as the Pt content in the solid increases. The results of the activity as a function of the Pt content in the bimetallic catalysts show a maximum value around 50% of Pt. An addition of Pt above this critical value leads to a small decrease of the catalytic activity.